Essential Statistics for Non-STEM Data Analysts Get to Grips with the Statistics and Math Knowledge Needed to Enter the World of Data Science with Python. - Li, Rongpeng (Packt Publishing, Limited, 2020)
Put your data science knowledge to work with this practical guide to statistics. You'll understand the working mechanism of each method used and find out how data science algorithms function. This book will help you learn the statistical techniques required for key model building and functioning using Python.